Cyber Crime Management among Students - Nte, Ngboawaji Daniel; Esq, Urowayinor Kelita; Enokie, Bribena Kelvin; Bienose, Onyeka (Faculty of Law, Universitas Negeri Semarang, 2020)
This study investigated examined the legal correlates of cybercrime management amongst higher institution students in Nigeria with special reference to some selected tertiary institutions in Delta State, Nigeria. A correlation approach of survey research design was adopted in this study. In order to address the problem of this study, seven research questions were raised and seven research hypotheses were formulated and tested at a .05 level of significance. This study revealed that the law can provide solutions to Cyber Crime management in Nigeria. Poverty is a factor responsible for cybercrime in Nigeria. The law can promote intellectual property and ensure privacy rights. There are existing laws that adequately address challenges relating to cybercrimes. The study revealed that youths who are mostly male are the major perpetrator of cyber-crimes and the crime can be committed at any time of the day. The study found that unemployment, poverty, absence of effectual law, and corruption are the major causes of cyber-crime in the study area. Based on the findings of this study, it was therefore recommended that collective vigilance detect and report to law enforcement agencies anyone suspected to be involved in cyber-crime. The Federal Government should empower the youths in terms of job creation and regularly engage the IT organizations to develop strategies to curtail cyber-crime.